2005
DOI: 10.1080/03639040500214662
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Skin Permeation of Sodium Naproxen Formulated in Pluronic F-127 Gels: Effect of Azone® and Transcutol®

Abstract: The objective of this study was to determine the penetration of sodium naproxen, formulated in Pluronic F-127 (PF-127) gels containing Azone and Transcutol as penetration enhancers, through human skin in vivo. It was found that the combination of Azone and Transcutol in PF-127 gels enhanced sodium naproxen penetration, with enhancement ratios of up to two fold compared with the formulation containing only Transcutol. These results were confirmed by TEWL and ATR-FTIR spectroscopy, suggesting a synergic action f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 28 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…It was found that the combination of Azone and Transcutol in Pluronic F127 gels enhanced sodium naproxen penetration, with enhancement ratios of up to two-fold compared with the formulation containing only Transcutol. This was confirmed by transepidermal water loss and attattentuated total reflectance FTIR spectroscopy analyses by Escobar-Chavez et al [16].…”
Section: Effect Of Additives On the Delivery Of Small Molecules From supporting
confidence: 53%
See 1 more Smart Citation
“…It was found that the combination of Azone and Transcutol in Pluronic F127 gels enhanced sodium naproxen penetration, with enhancement ratios of up to two-fold compared with the formulation containing only Transcutol. This was confirmed by transepidermal water loss and attattentuated total reflectance FTIR spectroscopy analyses by Escobar-Chavez et al [16].…”
Section: Effect Of Additives On the Delivery Of Small Molecules From supporting
confidence: 53%
“…Studies on PEO-PPO-based polymeric micelles for transdermal drug delivery have been widely carried out with Poloxamer 407 (Pluronic F127) and these studies mostly focused on small drug molecules in order of anti-inflammatory [8][9][10][11][12][13][14][15][16][17][18][19], analgesic [20], local anesthetic [21] and cardiac effectiveness [19,[22][23][24] and rarely focused on big molecules such as arginine vasopressin (AVP) and insulin [25,26].…”
Section: Peo-ppo Based Copolymers In Transdermal Drug Deliverymentioning
confidence: 99%
“…Poloxamers has been used as a delivery system of many drugs for ophthalmic (18,19), rectal (20,21), parenteral (22,23), topical (24), and transdermal (25,26) applications. Recently, PF-127 gel has been explored as a skin delivery system to several NSAIDs as naproxen (27), indometacin (28), piroxicam (26), diclofenac (29), among others, due to higher drug retention at the action site which leads to a sustained drug release and improved therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PF -127 water-based polymeric gels offer several other advantages over traditional bases in terms of ease of application, cosmetic acceptability (colorless and water-washable), good physicochemical stability and desirable drug release characteristics (25). PBDSs have been suggested as potential drug delivery systems for transdermal application of many antinflammatory drugs (26)(27) including naproxen, (28) indomethacin, (19,29) piroxicam (20) and diclofenac (30) due to higher drug retention at the site of action, sustained release and improved therapeutic effectiveness. This means that transdermal PBDSs may provide comparable antiinflammatory and analgesic activities to oral formulations while significantly reducing systemic side effects and gastrointestinal irritation associated with oral administration (26).…”
Section: Introductionmentioning
confidence: 99%